Degree of piRNA sharing and Piwi gene expression in the skeletal muscle of Piaractus mesopotamicus (pacu), Colossoma macropomum (tambaqui), and the hybrid tambacu - de Paula, Tassiana Gutierrez [UNESP] (2022)
PiRNAs are a class of small noncoding RNAs that, in their mature form, bind to Piwi proteins to repress transposable element activity. Besides their role in gametogenesis and genome integrity, recent evidence indicates their action in non-germinative tissues. We performed a global analysis of piRNA and Piwi gene expression in the skeletal muscle of juveniles pacu (Piaractus mesopotamicus), tambaqui (Colossoma macropomum), and the hybrid tambacu to evaluate the degree of piRNA sharing among these three genotypes. Total RNA was sequenced and analyzed using specific parameters of piRNAs by bioinformatics tools. piRNA and Piwi gene expression was analyzed by RT-qPCR. We detected 24 piRNA clusters common to the three genotypes, with eight shared between pacu and tambacu, three between pacu and tambaqui, and five between tambaqui and tambacu; seven, five, and four clusters were unique to pacu, tambacu, and tambaqui, respectively. Genomic localization and fold change values showed two clusters and 100 piRNAs shared among the three genotypes. The gene expression of four piRNAs was evaluated to validate our bioinformatics results. piRNAs from cluster 17 were higher in tambacu than pacu and piRNAs from cluster 18 were more highly expressed in tambacu than tambaqui and pacu. In addition, the expression of Piwis 1 and 2 was higher in tambacu and tambaqui than pacu. Our results open an important window to investigate whether these small noncoding RNAs benefit the hybrid in terms of faster growth and offer a new perspective on the function of piRNAs and Piwis in fish skeletal muscle.